Building and Improving Health Literacy in the 'New Normal' of Health Care Frameworks and Actions. - Lega, Federico (European Health Management in Transition Series., 2023)
Building and Improving Health Literacy in the 'New Normal' of Health Care identifies desirable paths of action to improve health literacy amongst patients, focusing on new technologies that could facilitate reducing health disparities. It is an essential read for policymakers and health care managers.